The assessment of physicochemical properties and macronutrient content of reclaimed soil material and hard coal ash 15 years after the experiment setup - Tomaszewicz, Tomasz; Chudecka, Justyna; Stankowski, Sławomir; Bashutska, Ulana; Gibczyńska, Marzena (Polish Journal of Agronomy, 2022)
This paper presents the results obtained during reclamation of hard coal ash. The model was developed by covering the layer of ash with layers containing ash, organic by-products and mineral fertilizers in 10 different combinations. The experiment on reclamation of hard coal ash was conducted in 2003 on the premises of Dolna Odra Power Station in Poland. The physicochemical parameters of top layers were well suited for cultivation on the reclaimed land. Particularly favourable was the introduction of fermented municipal sewage sludge to top layers. In this way, the appropriate structure of the analysed top layers was obtained, as manifested by good abundance of forms of magnesium, potassium and phosphorus available for vegetation. The obtained results demonstrate the process of accumulation of the available forms of magnesium, potassium and phosphorus in underlays when the fertile surface layer is supplemented with fermented municipal sewage sludge. The results obtained in the experiment indicate, that hard coal ashes can be managed in this way. Due to the long-term character of physicochemical and chemical properties of both top layers and underlays, the results presented here justify the continuation of the conducted reclamation experiment.